A weighted director network analysis of the big four banks on the Johannesburg Stock Exchange - Burgert A. Senekal; Karlien Stemmet (South African Journal of Business Management, 2019)
Background: Company director networks have been studied for many countries, including South Africa, from the perspective of network theory. However, most studies of company director networks focus on the overall structure of the network, that is, by conducting a macro-level analysis.Aim: In this study, we conducted a node-level analysis to investigate whether the four major South African banks, namely, Barclays Africa Group Ltd (now ABSA Group Limited), Nedbank Group Ltd, Standard Bank Group Ltd and FirstRand Ltd, occupy central roles in the company director network on the Johannesburg Stock Exchange (JSE).Setting: Social networks provide a vital source of information and are therefore an important field of study in business.Methods: We use degree-, betweenness- and closeness centrality, as well as strength, and a force-directed layout to investigate whether these four banks occupy key positions in the company director network on the JSE.Results: We show that these four banks occupy central roles on the JSE. The direct connections of these companies are also identified, and findings are compared to some overseas studies.Conclusion: This study concludes that the said four major banks occupy key positions on the JSE.
Keywords: 650